Troponin T isoform expression is modulated during Atlantic Halibut metamorphosis - Campinho, M. A. (2014)
Background: Flatfish metamorphosis is a thyroid hormone (TH) driven process which leads to a dramatic change from a symmetrical larva to an asymmetrical juvenile. The effect of THs on muscle and in particular muscle sarcomer protein genes is largely unexplored in fish. The change in Troponin T (TnT), a pivotal protein in the assembly of skeletal muscles sarcomeres and a modulator of calcium driven muscle contraction, during flatfish metamophosis is studied. Results: In the present study five cDNAs for halibut TnT genes were cloned; three were splice variants arising from a single fast TnT (fTnT) gene; a fourth encoded a novel teleost specific fTnTlike cDNA (AfTnT) expressed exclusively in slow muscle and the fifth encoded the teleost specific sTnT2. THs modified the expression of halibut fTnT isoforms which changed from predominantly basic to acidic isoforms during natural and T4 induced metamorphosis. In contrast, expression of red muscle specific genes, AfTnT and sTnT2, did not change during natural metamorphosis or after T4 treatment. Prior to and after metamorphosis no change in the dorso-ventral symmetry or temporal-spatial expression pattern of TnT genes and muscle fibre organization occurred in halibut musculature. Conclusion: Muscle organisation in halibut remains symmetrical even after metamorphosis suggesting TH driven changes are associated with molecular adaptations. We hypothesize that species specific differences in TnT gene expression in teleosts underlies different larval muscle developmental programs which better adapts them to the specific ecological constraints.